The Role of Brand Equity Antecedents in Strengthening Customer Loyalty with Relationship Equity as a Moderating Variable in Courier Service Companies - Irwan Chairuddin; Reni Dian Octaviani; Euis Saribanon; Indriyati Indriyati; Primadi Candra Susanto (Greenation Research & Yayasan Global Resarch National, 2026)
The purpose of this study is to examine the effect of digital content marketing (DCM), brand experience (BE), and price fairness (PF) on customer loyalty (CL) through brand equity (BEQ), with relationship equity (RE) as a moderating variable in courier service companies. This study was motivated by the importance of maintaining customer loyalty in the increasingly competitive courier service industry, where strong brand value is essential to sustain long-term customer relationships. The research applied a quantitative approach using a survey method involving 206 customers of courier service companies. Data were analyzed using the Structural Equation Modeling (SEM) method with SmartPLS 3.2.9. The findings reveal that digital content marketing, brand experience, and price fairness positively influence customer loyalty through brand equity. Although price fairness does not directly affect customer loyalty, it contributes indirectly through strengthening brand equity. In contrast, relationship equity was not found to significantly moderate the relationship between brand equity and customer loyalty. The novelty of this study lies in positioning digital content marketing as a strategic variable influencing customer loyalty both directly and indirectly through brand equity, while also examining the moderating role of relationship equity in the courier service context. The results provide managerial implications for courier service companies to strengthen customer loyalty by improving digital marketing strategies, enhancing customer brand experiences, and maintaining fair pricing policies to build stronger brand equity.